Methods to study the intestinal microbiota to address the disease in a more precise and personalized way - Burgos-Molina, Antonio Manuel; González Vidal, Alejandro; Mercado-Sáenz, Silvia; Alamilla Presuel, Juan Carlos; Ruiz-Gómez, Miguel José (My University, 2022)
FISH, clone collection, DGGE, PCR and metagenomics techniques contribute to the study of the human microbiota in a precise and effective way, constituting very useful diagnostic tools in precision medicine to address patient treatment in a personalized way.
Keywords: Aparato digestivo - Investigación; Microbiota; Precision medicine; Heath; Disease; Techniques